INCREASED PRODUCTIVITY OF HUMAN RESOURCES BASED ON KEY PERFORMANCE INDICATOR AND TRAINING - Kusnadi, Kusnadi (Dinasti International Journal of Digital Business Management, 2020)
This study aims to discuss methods in an effort to increase human resource productivity in a company based on Key Performance Indicators (KPI) and providing training. The concept of human resource development is a way that is carried out with the intention of making human resources a source of competitive advantage, based on practical experience that effective human resource development can increase work productivity, morale, and the potential in institutions, development programs. The assumption of work productivity can be seen as a mental attitude that always has the view that today's life must be better than yesterday and tomorrow must be better than today. Employees who have this attitude will be encouraged to be dynamic, creative, and open while remaining critical and responsive to new ideas and changes. This requires an appropriate human resource development strategy. Work productivity is the result of the interaction between work ability (ability) and motivation (motivation). Work motivation can be influenced by the physical condition, social conditions of the work environment, as well as the basic needs of employees. Productivity can be interpreted, among other things, from the aspect of individual appearance. Thus, employees who have the ability and high motivation in carrying out their duties will be able to support the organization by becoming a productive employee characterized by fulfilling job qualifications, positive job orientation, maturity, highly motivated, and able to get along effectively.